Investigation of Ultrasound on Some Germination Factors of Iranian (Bunium persicum Boiss.) and its Optimization - ali hasani; Mohammad Hadi Khoshtaghaza; Mohammad-Taghi Ebadi (علوم و فناوری بذر ایران, 2021)
In this study, the effect of ultrasound on the germination and vigor index of Iranian black cumin (Bunium persicum Boiss.), was studied. Response surface methodologhy and central composite design were used ti analyze the data and optimize the experiment. A factorial experiment based on completely randomized design was conducted. Experimental factors included time of ultrasound treatment (5, 7 and 9 minutes), ultrasonic power (130, 180 and 230 watts) and sonication temperatures (10, 20 and 30 °C) as well as control and germination percentage and seed vigor index were measured. The highest germination percentage and seed vigor index were determined by Response Surface Methodology (RSM). The results indicated significant effect of time and ultrasound power on studied traits, but temperature had no significant effect on them. The highest germination percentage (61%) and seed vigor index (800) were observed at 180 W and 7 min duration time and 20 °C. The lowest germination percentage (24.5%) and seed vigor index (462) were observed in 230 W ultrasound power, 9 min duration time and 20 °C. Also, the optimization results showed that the best points for power, time and temperature for achieving the highest values of germination percentage and seed vigor index were 175.47 W, 6.37 min and 19.36 °C, respectively and the output values (germination and seed vigor index) were obtained the this points 63.02% and 808.39 respectively. Finally it seems that the increasing or decreasing time and power of ultrasonication in a certain range decreases the seed germination percentage and vigor index.